Pharmacognosy Can natural products improve skin photoprotection? - Chiari-Andréo, Bruna Galdorfini [UNESP]; de Almeida, Fernanda Borges [UNESP]; Yamasaki, Paulo Renato [UNESP]; dos Santos, Jean Leandro [UNESP]; Corrêa, Marcos Antonio [UNESP]; Chin, Chung Man [UNESP]; Isaac, Vera Lucia Borges [UNESP] (FapUNIFESP (SciELO), 2020)
Due to increased UV radiation on the Earth’s surface, caused by depletion of the stratospheric ozone, people have become more susceptible to different types of skin damage, such as erythema, sunburns, and cancer; this is especially of concern in tropical countries. Thus, efforts to improve awareness as well as the use of sunscreen are increasing worldwide. However, synthetic UV filters have been associated with deleterious effects such as photosensitization. Natural products have been used by ancient cultures for several purposes, including protecting the skin from the sun. However, there is still doubt today whether photoprotection is a real phenomenom or whether it is simply tanning of the skin. Plants have self-protective mechanisms and produce secondary metabolites that can protect themselves from UV radiation. Yet, can phytochemical compounds protect human skin? This review discusses the paradoxical effect of chemical UV filters and the influence of phytochemicals in in vitro and in vivo tests of photoprotection.
Keywords: Chemical analysis; Natural compounds; Photoprotection; Sunscreen; Synergism